Implementasi Program Mutu Pendidikan Dalam Meningkatkan Budaya Akademik di Madrasah Aliyah Sunan Pandanaran (MASPA) Sardonoharjo Ngaglik Sleman DIY - Sri Haningsih (Islamic University of Indonesia, 2014)
The current paper aims at studying the implementation of quality assurance program at Madrasah Aliyah Sunan Pandanaran (MASPA) Sardonoharjo Ngaglik Sleman DIY. The quality assurance program run by MASPA is designed to give feedback to improve its academic quality. The subjects of the research are teachers and MASPA head of school. Using qualitative approach with observation and in-depth interview as data collection method, this study found that there is a moderate improvement on academic culture at MASPA, particularly on: 1) student presence level increases ?” 90%; 2) the increase of Kriteria Ketuntasan Minimal (KKM) fulfillment; 3) teachers presence level increases e” 90%; and d) better percentage of study completion of student.